Tingkat Pengetahuan dan Sikap Masyarakat Tentang Pencegahan Covid-19 di Desa Duwet Kabupaten Klaten - Dicky Sha-DK; Susi Endrawati (Indonesian Journal on Medical Science, 2023)
Coronavirus infectious disease 2019 (COVID-19) is caused by a new coronavirus. At the end of 2019, a case of pneumonia with no known cause was detected in Wuhan, China. Conducted virological and epidemiological studies show that the main transmission of COVID-19 comes from someone who is symptomatic to other individuals around them via droplets. The purpose of this study is to describe the knowledge and attitudes of the people in Duwet Village, Klaten Regency regarding COVID-19. This research is a descriptive research with a survey method. A total of 75 people were used as samples in this study and were selected by purposive sampling technique. The results of the study presented the data if most respondents were male 50.67% (38 respondents), most were 17-20 years old reaching 36% (27 respondents), most had education up to high school as much as 60% (45 respondents), and most of them are students, reaching 26.67% (20 respondents). The conclusion of the research results regarding the knowledge and attitudes of the people of Duwet Village, Klaten Regency, is in the good category for knowledge indicators (85.33%) and attitude indicators (87%).